MEASURING RATIONALITY IN THE PERFORMANCE MEASUREMENT PROCESS AND ALLOCATING RESOURCES OF PUBLIC SECTOR ORGANIZATIONS - I Putu Julianto; Made Aristia Prayudi (Berkala Akuntansi dan Keuangan Indonesia, 2016)
This study extends prior Balanced Scorecard (BSC) research by examining the role of rational (cognitive) and non-rational (political power) aspect on both BSC-based performance measurement and resource allocation decision making in public sector organization. We conduct an experiment using 70 undergraduate accounting students at a large public university in Bali Province asked to assume the role of a governmental auditor whose task was to evaluate the performance of two departments in a fictitious local government in Indonesia. Participants were then requested to make recommendation about how additional bonus should be allocated to the departments. As the result, we find that cognitive aspect do have impact on performance evaluation, but not in bonus allocation, decision making. Meanwhile, political power appears to have significant effect on the resource allocation decisions based on BSC mechanism. However, it can’t be hold in performance evaluation judgement. Hence, the findings allow concluding that the process of performances measurement in public sector is more rational than resources allocation ones.